2012
DOI: 10.1111/j.1471-4159.2012.07757.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of thallium diethyldithiocarbamate for mapping CNS potassium metabolism and neuronal activity: Tl+‐redistribution, Tl+‐kinetics and Tl+‐equilibrium distribution

Abstract: J. Neurochem. (2012) 122, 106–114. Abstract The potassium (K+) analogue thallium (Tl+) can be used as a tracer for mapping neuronal activity. However, because of the poor blood–brain barrier (BBB) K+‐permeability, only minute amounts of Tl+ enter the brain after systemic injection of Tl+‐salts like thallium acetate (TlAc). We have recently shown that it is possible to overcome this limitation by injecting animals with the lipophilic chelate complex thallium diethyldithiocarbamate (TlDDC), that crosses the BBB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…At the cellular level, we found complex heterogeneous Tl + uptake patterns incompatible with passive diffusion of TlDDC into the tissue supporting our conclusion from previous studies that Tl + is released from TlDDC before neuronal or astrocytic uptake. 10, 11, 24 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…At the cellular level, we found complex heterogeneous Tl + uptake patterns incompatible with passive diffusion of TlDDC into the tissue supporting our conclusion from previous studies that Tl + is released from TlDDC before neuronal or astrocytic uptake. 10, 11, 24 …”
Section: Discussionmentioning
confidence: 99%
“…To this end, animals should preferentially be perfused 5 to 15 minutes after Tl + injection. 11 When net transmembrane Tl + fluxes cease, differences in activity-dependent Tl + fluxes cannot be detected. For mapping spatial patterns of neuronal damage, no such limitation exists.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…K + -analogus like the univalent thallium ion Tl + can be used, therefore, as tracers for imaging neuronal activity (Landowne 1975 ; Goldschmidt et al 2004 ). Furthermore, we have recently shown that the lipophilic chelate complex thallium diethyldithiocarbamate (TlDDC) passes the blood–brain barrier and can be used for mapping neuronal activity with single cell resolution in freely moving, behaving rodents, with short stimulation times of 5 min (Macharadze et al 2009 , 2012 ; Goldschmidt et al 2010 ; Wanger et al 2012 ; Lison et al 2013 ; Stöber et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%